Colonoscopy Quality and Adherence to Postpolypectomy Surveillance Guidelines in an Underinsured Clinic System - Jaison John; Abdul Al-Douri; Bretta Candelaria; Saurin Gandhi; Paul Guzik; Brent Herndon; Christopher Kim; Nicole Kluz; Jennifer Thompson; Jessica Trevino; Victoria Valencia; Michael Pignone (Gastroenterology Research and Practice)
Background. Delivery of high-quality colonoscopy and adherence to evidence-based surveillance guidelines is essential to a high-quality screening program, especially in safety net systems with limited resources. We sought to assess colonoscopy quality and ensure appropriate surveillance in a network of safety net practices. Methods. We identified age-eligible patients ages 50-75 within a Federally Qualified Health Center (FQHC) clinic system with evidence of colonoscopy in preceding 10 years. We performed chart reviews to assess key aspects of colonoscopy quality: bowel preparation quality, evidence of cecal intubation, cecal withdrawal time, and the adenoma detection rate. We then utilized established guidelines to assess and revise surveillance colonoscopy intervals, determine whether appropriate surveillance had taken place, and schedule overdue patients as appropriate. Results. Of 26,394 age-eligible patients, a total of 3,970 patients had evidence of prior colonoscopy and 1,709 charts were selected and reviewed. Mean age was 57, 54% identified as women and 51% identified as Hispanic. Of 1709 colonoscopies reviewed, 77% had data on bowel preparation, and of those, 85% had adequate preparation quality. Cecal intubation was documented in 89% of procedures. Adequate cecal withdrawal time was documented in 59% of those with documented cecal intubation. Overall adenoma detection rate was 42%. Initial surveillance interval was clearly stated in 72% (n=1238) of procedures. Of these, initial recommended intervals were too short in 24.5% (n=304) and too long in 3.6% (n=45). A total of 132 patients (10.7%) were overdue for appropriate surveillance and were referred for follow-up colonoscopy. Conclusions. Overall, the quality of screening colonoscopy was high, but reporting was incomplete. We found fair adherence to evidence-based surveillance guidelines, with significant opportunities to extend surveillance intervals and improve adherence to best practices.